2022
DOI: 10.3389/fonc.2022.832385
|View full text |Cite
|
Sign up to set email alerts
|

Machine-Learning-Based Bibliometric Analysis of Pancreatic Cancer Research Over the Past 25 Years

Abstract: Machine learning and semantic analysis are computer-based methods to evaluate complex relationships and predict future perspectives. We used these technologies to define recent, current and future topics in pancreatic cancer research. Publications indexed under the Medical Subject Headings (MeSH) term ‘Pancreatic Neoplasms’ from January 1996 to October 2021 were downloaded from PubMed. Using the statistical computing language R and the interpreted, high-level, general-purpose programming language Python, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…These results reflected that the United States had made great contributions and established its leading position in the field of NDDS for PC. In addition to the research topic of NDDS for PC, similar results were also obtained in the bibliometric analysis of other topics such as “pancreatic cancer” ( Wang and Herr, 2022 ), “pancreatic stellate cells” ( Yang et al, 2022b ), and “inhalable nanosystems” ( Huang et al, 2021 ). As for the cooperation among countries, it could be seen from Figure 3C that among the 20 countries with the most publications, the United States and China had the closest cooperation with other countries/regions; The United States, European countries (e.g., Italy and France), and Asian countries (e.g., China, India, and Saudi Arabia) were still the most important parts of the national cooperation landscape, and extensive cooperation had been established between them, but the cooperation of other developing countries was still relatively weak, and these countries needed to further cooperate to promote the development of NDDS for PC research field worldwide.…”
Section: Discussionsupporting
confidence: 62%
“…These results reflected that the United States had made great contributions and established its leading position in the field of NDDS for PC. In addition to the research topic of NDDS for PC, similar results were also obtained in the bibliometric analysis of other topics such as “pancreatic cancer” ( Wang and Herr, 2022 ), “pancreatic stellate cells” ( Yang et al, 2022b ), and “inhalable nanosystems” ( Huang et al, 2021 ). As for the cooperation among countries, it could be seen from Figure 3C that among the 20 countries with the most publications, the United States and China had the closest cooperation with other countries/regions; The United States, European countries (e.g., Italy and France), and Asian countries (e.g., China, India, and Saudi Arabia) were still the most important parts of the national cooperation landscape, and extensive cooperation had been established between them, but the cooperation of other developing countries was still relatively weak, and these countries needed to further cooperate to promote the development of NDDS for PC research field worldwide.…”
Section: Discussionsupporting
confidence: 62%
“…As far as countries for publication of papers are considered, a bibliometric analysis of autophagy showed that China and the United States were the most productive countries (27). Again, one bibliometric study on mitophagy (34) and the other bibliometric study on pancreatic cancer research (35) arrived the same conclusion. Our results also showed that China and the United States were the most frequent publishers in the field of autophagy and pancreatic cancer.…”
Section: Discussionmentioning
confidence: 85%
“…Previous bibliometric studies has focused on the research of autophagy ( 27 ), mitophagy ( 34 ), pancreatic cancer ( 35 ), tumor microenvironment of pancreatic cancer ( 36 ), and pancreatic neuroendocrine tumors ( 37 ). As a novel perspective, we conducted a bibliometric analysis based on literature related to autophagy of pancreatic cancer from 2011 to 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Our methodology incorporates a computer-aided text analysis within the framework of bibliometric analysis, a technique increasingly favored across various disciplines, particularly in medicine, because of its ability to interpret semantic meaning [23]. Key to our analysis was text mining and unsupervised machine learning topic modeling facilitated by a Python algorithm, methods known to offer critical insights into existing studies and future research directions [24].…”
Section: Overviewmentioning
confidence: 99%